Hypertension: Impact of Lifestyle Modifications on Blood Pressure Control - Imran Khan, Faizan Saqib, Mohsina Hamid, Ashok Kumar, Muhammad Wali, Muhammad Kashif Iltaf, Bilal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective was to find out what variables and changes in lifestyle were linked to better control of blood pressure in individuals who were given antihypertensive medication. Study Design: Cross-sectional study Methods: Total 360 patients of both genders were presented in this study. Individual questions were used to conduct an initial assessment of the patients' lifestyles. At4,8, and 12 weeks, participants were asked to fill out a follow-up survey. After the data was imported into EpiInfo and analysed using SPSS version 24, binary logistic and multivariate logistic regression were employed to identify relevant variables. Results: There were majority 215 (59.7%) males and 145 (40.3%) females among all cases. Mean age of the cases was 48.9 years and had mean BMI 25.7 kg/m2. 160 (44.4%) patients were educated. 190 (52.8%) cases had poor socio-economic status. Mean duration of hypertension was 4.8 years. Approximate 33.3% of the population followed recommendations to alter their way of life. The independent factors that were found to have a significant impact on the likelihood of sticking to lifestyle modification practices were having a high level of education (AOR = 0.202 95% CI (0.079-0.358)), having a good understanding of the subject (AOR = 3.232 95% CI (1.62- 6.287)), believing in one's own abilities (AOR = 3.49895% CI (1.62- 6.287)), having a strong social support system (AOR = 8.498 95% CI (4.164- 16.274)), and having a positive relationship with one's doctor (AOR = 2.305 95% CI (1.208- 4.537)). Conclusion: One-third of individuals adopted the lifestyle modifications. Information, self-efficacy, social support, and patient–physician relationships important. Hypertension patients should be educated and empowered to change their lifestyles by healthcare groups. Keywords: adherence, lifestyle modification, hypertension